2020
DOI: 10.3389/fneur.2020.544434
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Neuromyelitis Optica Spectrum Disorder – Reciprocal Effects and Practical Recommendations: A Systematic Review

Abstract: Introduction: Neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory disorder of the central nervous system characterized by severe, antibody-mediated astrocyte loss with secondary demyelination and axonal damage, predominantly targeting optic nerves and the spinal cord. Recent publications have alluded to increased disease activity during pregnancy, and adverse maternal and fetal outcomes in patients with NMOSD. Our objective was to systematically review published literature to help counsel and man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 71 publications
0
18
0
Order By: Relevance
“…[3] As is the case with MS, women with NMOSD face an increased risk of postpartum relapse, [4] however data on relapse rate during pregnancy is mixed. Prior studies have demonstrated stable or increased rate of relapse during pregnancy [4,5] whereas a 2021 study of 46 women with aquaporin-4 seropositive NMOSD, 30 with MOG associated disease and 13 with double negative NMOSD [6] demonstrated lower relapse rate during pregnancy as compared to the pre-pregnancy period. In this study, only the aquaporin-4 seropositive NMOSD patients demonstrated increased postpartum relapse compared to prepregnancy period, but numbers were small.…”
Section: Overview Of Multiple Sclerosis and Neuromyelitis Optica Spectrum Disorder And Pregnancymentioning
confidence: 99%
“…[3] As is the case with MS, women with NMOSD face an increased risk of postpartum relapse, [4] however data on relapse rate during pregnancy is mixed. Prior studies have demonstrated stable or increased rate of relapse during pregnancy [4,5] whereas a 2021 study of 46 women with aquaporin-4 seropositive NMOSD, 30 with MOG associated disease and 13 with double negative NMOSD [6] demonstrated lower relapse rate during pregnancy as compared to the pre-pregnancy period. In this study, only the aquaporin-4 seropositive NMOSD patients demonstrated increased postpartum relapse compared to prepregnancy period, but numbers were small.…”
Section: Overview Of Multiple Sclerosis and Neuromyelitis Optica Spectrum Disorder And Pregnancymentioning
confidence: 99%
“…In a systematic review, it has been reported that maternal symptoms during pregnancy were sensorial abnormalities, neuropathic pain, motor weakness, visual symptoms, incontinence and spasticity [15].…”
Section: Discussionmentioning
confidence: 99%
“…NMOSD obstetric outcomes data are needed, with limited case series inconclusive to date. 33 Additional challenges exist in managing women with NMOSD during pregnancy. NMOSD is relatively rare and less well known to many nonneurologists/ophthalmologists.…”
Section: Pregnancy and Neuromyelitis Optica Spectrum Disorder Outcomesmentioning
confidence: 99%